The Transformation of the Middle East and the Future of NATO's Partnerships - Pia Niedermeier (Stiftung Wissenschaft und Politik (SWP), 2011)
On October 31, 2011, NATO terminated its first mission in the Arab world: Operation Unified Protector in Libya. Although the mission revealed diplomatic disunity within the Alliance as well as a tremendous lack of military capabilities in Europe, NATO is widely credited with having successfully saved lives and for protecting civilians. Beyond the immediate challenges in Libya, NATO allies will have to re-evaluate their relationships with countries in the region in light of the Arab Spring. One tool to do so is the adaptation of NATO's long-standing partnerships in the region: the Mediter-ranean Dialogue (MD) and the Istanbul Cooperation Initiative (ICI). While allies have agreed on some principles of such adaption at their summit in Berlin in April 2011, most measures are still awaiting implementation. Certainly, NATO can contribute toward stabilization in the region and toward supporting the democratic movements in the region. However, its role will likely be a limited and complementary one, as sug-gested by an examination of NATO's self-proclaimed goals - democratic transformation of the armed forces, regional security, and interoperability.
Keywords: 320